2006
DOI: 10.1128/jb.188.2.687-693.2006
|View full text |Cite
|
Sign up to set email alerts
|

Phenotype Microarray Profiling of Staphylococcus aureus menD and hemB Mutants with the Small-Colony-Variant Phenotype

Abstract: Standard biochemical tests have revealed that hemin and menadione auxotrophic Staphylococcus aureus smallcolony variants (SCVs) exhibit multiple phenotypic changes. To provide a more complete analysis of the SCV phenotype, two genetically defined mutants with a stable SCV phenotype were comprehensively tested. These mutants, generated via mutations in menD or hemB that yielded menadione and hemin auxotrophs, were subjected to phenotype microarray (PM) analysis of over 1,500 phenotypes (including utilization of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
106
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 115 publications
(107 citation statements)
references
References 29 publications
1
106
0
Order By: Relevance
“…On solid media, the unique SCV phenotype may be recognized visually if cells grow unambiguously as pinpoint colonies. However, naturally occurring SCVs are unstable, and most studies on the SCV phenotype are based upon stable site-directed mutants in electron transport (2,19,23,26,27). Because the mutations in clinical strains have yet to be defined, these mutants do not necessary reflect the complete phenotype of natural SCVs.…”
Section: Discussionmentioning
confidence: 99%
“…On solid media, the unique SCV phenotype may be recognized visually if cells grow unambiguously as pinpoint colonies. However, naturally occurring SCVs are unstable, and most studies on the SCV phenotype are based upon stable site-directed mutants in electron transport (2,19,23,26,27). Because the mutations in clinical strains have yet to be defined, these mutants do not necessary reflect the complete phenotype of natural SCVs.…”
Section: Discussionmentioning
confidence: 99%
“…Phenotype microarrays allow the analysis of hundreds of physiological tests in parallel, thereby enabling the fast and accurate identification of novel traits linked to genetic alterations (1,34,40). Remarkably, a comparison of the quadruple mutant HB0842 with the isogenic wild type revealed only three significant differences in growth: the mutant grew better than wild type in the presence of chloramphenicol, neomycin, and piperacillin.…”
Section: Construction Of Ecf Mutant Strains In Ncib3610mentioning
confidence: 99%
“…Genetically stable mutants in the hemin biosynthetic gene, hemB, or menadione biosynthetic gene, menD, have been characterized as having lower capacities for oxidative phosphorylation. They revealed many phenotypic changes (e.g., decreased pigmentation) and unusual biochemical characteristics as consequences of altered metabolic and energy-dependent pathways (4,5,21,38,46,48,49).In a previous study, it was found that some TCA cycle genes were upregulated in biofilms, particularly the succinate dehydrogenase genes (sdhCAB) but also the 2-oxoglutarate dehydrogenase (odhA) and the succinyl-coenzyme A (CoA) synthetase (sucC) genes (32, 33). The succinate dehydrogenase (EC 1.3.99.1) is part of the nonoxidative branch of the TCA cycle and is directly linked to the respiratory chain.…”
mentioning
confidence: 99%
“…Genetically stable mutants in the hemin biosynthetic gene, hemB, or menadione biosynthetic gene, menD, have been characterized as having lower capacities for oxidative phosphorylation. They revealed many phenotypic changes (e.g., decreased pigmentation) and unusual biochemical characteristics as consequences of altered metabolic and energy-dependent pathways (4,5,21,38,46,48,49).…”
mentioning
confidence: 99%